2021
DOI: 10.1097/hnp.0000000000000384
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acupressure on Blood Pressure Level and Pulse Rate in Individuals With Essential Hypertension

Abstract: A total of 91 people including 47 in the intervention group and 44 in the placebo group were included to a randomized controlled study. It can be asserted that acupressure, applied to the Neiguan (PC 6) acupuncture point in individuals with essential hypertension, provides blood pressure regulation and is effective for management of numerous hypertension-related symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
5
0
2
Order By: Relevance
“…However, contrary to our expectations, moxibustion and acupressure showed similar effects on reducing blood pressure, suggesting that the stimulation of acupoints itself may contribute to the observed blood pressure reduction. Our findings align with previous studies that have reported decreased blood pressure with both moxibustion [12,16] and acupressure [9,10] administered by practitioners to hypertensive patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, contrary to our expectations, moxibustion and acupressure showed similar effects on reducing blood pressure, suggesting that the stimulation of acupoints itself may contribute to the observed blood pressure reduction. Our findings align with previous studies that have reported decreased blood pressure with both moxibustion [12,16] and acupressure [9,10] administered by practitioners to hypertensive patients.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies, including a systematic review, have reported self-acupressure as an effective self-management method for various health conditions, including stress, sleep disturbance, and quality of life, which were measured in this study [42][43][44][45]. Moxibustion and acupressure share the same therapeutic mechanisms based on the meridian theory [9,13,14]. Therefore, we compared the effects of self-moxibustion with acupressure as a positive control to investigate the feasibility of self-management for hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Cardiovascular Health and Diseases in China reported that there were 330 million Chinese patients with cardiovascular diseases, 245 million of whom had essential hypertension [1]. Thus, the disease constitutes a serious danger to the health and lives of Chinese people.…”
Section: Introductionmentioning
confidence: 99%
“…Durasi terapi akupresur adalah sepuluh menit sampai tiga puluh menit dan dilakukan tiga kali seminggu. 5,6 Lokasi titik akupresur dapat dilihat pada gambar 4.…”
unclassified